Effectiveness of attendance system using radio frequency identification (RFID) with "Drive Thru" technique - Nurul Husna Abdul Kahar (Tanjong Malim, 2018)
Effectiveness of attendance system using radio frequency identification (RFID) with "Drive Thru" technique by Nurul Husna Abdul Kahar